Five‐year mortality outcomes in patients with chronic kidney disease undergoing percutaneous coronary intervention. Issue 4 (13th August 2016) - Patel, Agam D.; Ibrahim, Mohammed; Swaminathan, Rajesh V.; Minhas, Irfan U.; Kim, Luke K.; Venkatesh, Prashanth; Feldman, Dmitriy N.; Minutello, Robert M.; Bergman, Geoffrey W.; Wong, S. Chiu; Singh, Harsimran S.
Abstract : Objective: To examine peri‐procedural and long‐term outcomes in patients with chronic kidney disease (CKD) undergoing percutaneous coronary interventions (PCI). Background: Patients with advanced CKD are considered high risk when undergoing PCI. Limited published data exist on quantifying risk and assessment of long‐term outcomes after PCI in this group. Methods: Examining the Cornell Coronary Registry, we prospectively collected data of 6, 478 consecutive patients who underwent elective or urgent PCI between 2009 and 2013. Patients were grouped into CKD stages by estimated glomerular filtration rate (eGFR) according to KDOQI guidelines. Procedural and 30‐day outcomes are reported with assessment of long‐term differences in 5‐year all‐cause mortality. Results: Patients were grouped by CKD stages: 1, 351 patients with eGFR ≥90 mL/min/1.73 m 2 (stage 1), 2, 882 with eGFR 60–89 (stage 2), 1, 742 with eGFR 30–59 (stage 3), 191 with eGFR 15–29 (stage 4), and 312 with eGFR <15 or on dialysis (stage 5). The incidence of post‐procedural acute heart failure, stroke, new dialysis requirement, transfusions, and bleeding events were higher in patients with greater CKD stage ( P  < 0.05). Five‐year Kaplan–Meier overall survival among CKD stages 1–5 was 98.1, 95.5, 91.8, 82.5, and 76.9%, respectively ( P  < 0.001 by log‐rank test). The hazard ratios of all‐cause mortality for CKD stages 2–5 as compared to stage 1 by multivariate Cox regression analysis were as follows: 1.32 ( P  = 0.26), 2.04 ( P  < 0.01), 2.79 ( P  < 0.01), and 5.49 ( P  < 0.001). Conclusion: Among patients undergoing PCI, lower GFR is associated with decreased long‐term survival. © 2016 Wiley Periodicals, Inc.